VNS Implantation Effectivness in Drug-Resistant Epilepsy - Abduvoyitov, Bobur (American Journal of Bioscience and Clinical Integrity, 2025)
Despite significant advances in epileptology, treatment-resistant epilepsy accounts for approximately 30% of all forms of this disease. Even taking into account the wide range of modern drug and non-drug treatment methods, there remains a significant proportion of patients with treatment-resistant epilepsy, in whom antiepileptic drugs are ineffective and surgical treatment is impossible. In this group of patients, pharmacotherapy remains relevant with the search for new effective antiepileptic drugs, as well as the search for alternative methods, one of which is vagus nerve stimulation. The authors present a literature review devoted to the indications for use, efficacy, and tolerability of the vagus nerve stimulation method in epilepsy, and a description of an observed case of the effectiveness of this method in a patient with a resistant form of epilepsy.